Discoidin Domain Receptor-1 Regulates Calcific Extracellular Vesicle Release in Vascular Smooth Muscle Cell Fibrocalcific Response via TGF-β Signaling - Krohn, Jona B. (Arterioscler Thromb Vasc Biol, 2016)
OBJECTIVE: Collagen accumulation and calcification are major determinants of atherosclerotic plaque stability. Extracellular vesicle (EV)-derived microcalcifications in the collagen-poor fibrous cap may promote plaque rupture. In this study, we hypothesize that the collagen receptor discoidin domain receptor-1 (DDR-1) regulates collagen deposition and release of calcifying EVs by vascular smooth muscle cells (vSMCs) through the TGF-β pathway. APPROACH AND RESULTS: VSMCs from the carotid arteries of DDR-1(−/−) mice and wild type littermates (n=5–10 per group) were cultured in normal or calcifying media. At days 14 and 21, vSMCs were harvested and EVs isolated for analysis. Compared to wild type, DDR-1(−/−) vSMCs exhibited a 4-fold increase in EV release (p<0.001) with concomitantly elevated alkaline phosphatase (ALP) activity (p<0.0001) as a hallmark of EV calcifying potential. The DDR-1(−/−) phenotype was characterized by increased mineralization (Alizarin Red S and Osteosense, p<0.001 and p=0.002, respectively) and amorphous collagen deposition (p<0.001). We further identified a novel link between DDR-1 and the TGF-β pathway previously implicated in both fibrotic and calcific responses. An increase in TGF-β1 release by DDR-1(−/−) vSMCs in calcifying media (p<0.001) stimulated p38 phosphorylation (p=0.02) and suppressed activation of Smad3. Inhibition of either TGF-β receptor-I or phospho-p38 reversed the fibrocalcific DDR-1(−/−) phenotype, corroborating a causal relationship between DDR-1 and TGF-β in EV-mediated vascular calcification. CONCLUSION: DDR-1 interacts with the TGF-β pathway to restrict calcifying EV-mediated mineralization and fibrosis by vSMCs. We therefore establish a novel mechanism of cell-matrix homeostasis in atherosclerotic plaque formation.